Young offenders and the law : how the law responds to youth offending - Arthur, Raymond (Routledge, 2010)
How does the law deal with young offenders, and to what extend does the law protect and promote the rights of young people in conflict with the law? This title addresses these central issues and examines the legal response to the phenomenon of youth offending, and the contemporary forces that shape the law